SPATIAL PATTERN OF SUBSIDIZED HOUSING IN BODETABEK REGION - Adi, Luwi Wahyu; Wibowo, Adi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The development of cities and regions is linked to housing development. The triggering factor is the increasing need for housing due to population growth. The Indonesian government has implemented the obligation to fulfill housing needs, one of which is through housing subsidies. However, the housing sector is one of the most complex sectors because it involves many stakeholders. Solving housing problems is also not easy to do. Moreover, the housing is located in an area with high population density and is a buffer for the capital such as Bodetabek. This research aims to find out what the spatial pattern of subsidized housing in the Bodetabek area looks like. Some of the methods used to determine the spatial pattern of subsidized housing are kernel density, density-base clustering and average nearest neighbor analysis. The results have shown that subsidized housing forms a density distribution pattern in the Bodetabek area. The distribution pattern has been divided into 5 classes, namely very low, low, medium, high and very high. In general, subsidized housing in Bodetabek has fallen into the clustering category. In addition, subsidized housing has been divided into 5 (five) large clusters. The clusters are Rajeg Cluster, Tigaraksa-Cisoka-Solear Cluster, Ciseeng-Ciampea-Kemang-Rancabungur Cluster, Cileungsi-Klapanunggal-Cibarusah-Serang Baru Cluster and Cibitung-Karang Bahagia-North Tambun Cluster. These patterns can be used as a database for development planning in the Bodetabek area. The development planning adjusts the segment of beneficiaries of subsidized housing, namely low-income communities.